The Financial Economic Development Agenda of the SADC Region - Kgomo, Dintuku Maggie; Ncanywa, Thobeka (International Journal of Economics and Financial Issues, 2025)
Financial markets have been used in developing economies to raise and maintain these economies social stability level, and to facilitate economic development. Economic development is about the upliftment of the living standards and freedom of the citizens by upgrading the quality of human lives. The study strove to realise the objective of determining if different forms of financial markets can influence economic development in selected Southern Africa Development Community (SADC) countries. Panel econometric techniques were utilised and periods examined spanned from 2007 to 2021. Economic development may not be quantified using a single indicator. Economic development as the dependent variable was measured by the Economic Development Index (EDI) which was constructed using indicators such as the Human Development Index, Economic Complexity Index and Gross Domestic Product per capita. The money market, stock market and foreign exchange market were found to negatively influence EDI in the long-run. Financial markets can be stated to influence the development and economic performance of the selected SADC countries. Based on the findings, it is recommended that monetary authorities and regulatory authorities ensure that the monetary, fiscal, and financial policies are well managed, and that these policies are implemented to develop the social and economic level of the country.